Sustainability Of Community Food Barns: A Case Study Of Traditional Groups In Yogyakarta - Wirakusuma, Gilang; Sugiyarto, Sugiyarto (Agro Ekonomi, 2025)
Community food barns (lumbung) are one of the local institutions established to maintain food security in rural areas. In line with this objective, several studies have been conducted to address concerns about the declining sustainability of traditional community food barns, which are vital for ensuring food security and preserving cultural heritage in rural areas. This indicates that there is an urgent need to strengthen local food systems and support rural development initiatives by assessing institutional factors influencing their sustainability. Therefore, this study aims to evaluate the sustainability of community food barns and identify the dominant factors. Multidimensional Scaling analysis was used to measure sustainability and determine the dominant influential factors. The study population comprised 32 respondents from 32 groups of barns spread across the Special Region of Yogyakarta. A total of 3 dimensions were involved in the analysis, namely institutional, socio-cultural, and economic. The analysis results showed that the sustainability of community food barns was classified as the 'quo' criterion. This indicated that the current status of the sustainability of traditional barns could not develop naturally to a higher level without intervention. In addition, the dominant factors determining the level of sustainability were identified from the 3 dimensions. Strategies to improve sustainability could be pursued from various aspects. Based on the results, the current study showed that fostering farmer group activities and enhancing collaboration with various stakeholders were essential for sustaining traditional community food barns. These efforts strengthened institutional support, promoted knowledge sharing, and ensured collective resource management, ultimately contributing to rural development and agricultural resilience.